2012
DOI: 10.1080/10934529.2012.672301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different wastewater treatments for removal of selected endocrine-disruptors from paper mill wastewaters

Abstract: There is increasing concern about chemical pollutants that have the ability to mimic hormones, the socalled endocrine disrupting compounds (EDCs). One of the main reasons for concern is the possible effect of EDCs on human health. EDCs may be released into the environment in different ways, and one of the most significant sources is industrial wastewater. The main objective of this research was to evaluate the treatment performance of different wastewater treatment procedures (biological treatment, filtration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…This can result in the release of suspended solids and nutrients, such as nitrogen and phosphorus, which can lead to eutrophication of the receiving water bodies and oxygen depletion (Thompson et al 2001). Endocrine disruptors may be also present in the wastewater (Balabanic et al 2012), though relatively little is known about potential endocrine disruption effects of paper mill effluents on aquatic organisms. For example, plant sterols (phytosterols) may act as disrupters of the hormonal and biochemical systems of aquatic organisms (Kostamo and Kukkonen 2003).…”
mentioning
confidence: 99%
“…This can result in the release of suspended solids and nutrients, such as nitrogen and phosphorus, which can lead to eutrophication of the receiving water bodies and oxygen depletion (Thompson et al 2001). Endocrine disruptors may be also present in the wastewater (Balabanic et al 2012), though relatively little is known about potential endocrine disruption effects of paper mill effluents on aquatic organisms. For example, plant sterols (phytosterols) may act as disrupters of the hormonal and biochemical systems of aquatic organisms (Kostamo and Kukkonen 2003).…”
mentioning
confidence: 99%
“…Particularly, Sevimli (2005) and Balabaniç et al (2012) reported a 20% COD removal improvement when this treatment combination was applied to effluents from a biologically treated corrugated board factory and a recycled paper mill. In turn, Ko et al (2009) reported an increase of color removal, but no effect on the reduction of the COD, when they treated diluted weak black liquor from a hardwood kraft pulp mill.…”
Section: Combination Of Ozone and H 2 O 2 In An Oxidation Treatment (mentioning
confidence: 96%
“…Considering biological treatment is not able to remove bio-recalcitrant compounds (Balcioglu et al 2003;Bijan and Mohseni 2004), new trends are focused on incorporating other processes like advanced oxidation ones (AOPs) (Balabaniç et al 2012;Balcioglu et al 2003;Bijan and Mohseni 2004;Hermosilla et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOPs applied to nonylphenol comprise ozonation (Table S4), electron beam irradiation (Table S5) and comparative stud-ies of different AOPs such as Fentonbased, photocatalysis and ozonation (Table S6). Photo-Fenton and ozonation were compared regarding nonylphenol removal in two reports (Balabanič et al, 2012;Bertanza et al, 2010), one of them comparing also Fenton and heteroge-neous photocatalysis. Using wastewater as matrix, photo-Fenton was the most efficient AOP (Balabanič et al, 2012).…”
Section: Nonylphenol and Octylphenolmentioning
confidence: 99%